ChemInform Abstract: Taming the Carboxyl Group for Directed Carbometalation: Observations on the Use of Anions, Dianions and Ester Enolates. Issue 2 (January 2015) - Desrat, Sandy; Gray, Philip J.; Penny, Matthew R.; Motherwell, William B.
Abstract The copper‐mediated directed metalation of allenic acid (I) and ester (XIV) is investigated to yield β, γ‐unsaturated products (III) and (XV) regioselectively.